Paediatric acute lymphadenitis: Emergency department management and clinical course. Issue 8 (21st September 2019) - Long, Michelle; Reddy, Deepti N; Akiki, Salwa; Barrowman, Nicholas J; Zemek, Roger
Abstract: Objectives: To describe clinical characteristics and management of acute lymphadenitis and to identify risk factors for complications. Methods: Health record review of children ≤17 years with acute lymphadenitis (≤2 weeks) in a tertiary paediatric emergency department (2009–2014); 10% of charts were reviewed by a blinded second reviewer. Multivariate logistic regression identified factors associated with intravenous antibiotic treatment, unplanned return visits warranting intervention, and surgical drainage. Results: Of 1, 023 health records, 567 participants with acute lymphadenitis were analyzed. The median age = 4 years (interquartile range [IQR]: 2 to 8 years), and median duration of symptoms = 1.0 day (IQR: 0.5 to 3.0 days). Cervical lymphadenitis was most common. Antibiotics were prescribed in 73.5% of initial visits; 86.9% of participants were discharged home. 29.0% received intravenous antibiotics, 19.3% had unplanned emergency department return visits, and 7.4% underwent surgical drainage. On multivariate analysis, factors associated with intravenous antibiotic use included history of fever (odds ratio [OR]=2.07, 95% confidence interval [CI]: 1.11 to 3.92), size (OR=1.74 per cm, 95% CI: 1.44 to 2.14), age (OR=0.84 per year, 95% CI: 0.76 to 0.92), and prior antibiotic use (OR=4.45, 95% CI: 2.03 to 9.88). The factors associated with unplanned return visit warranting intervention was size (OR=1.30 per cm, 95% CI: 1.06 to 1.59) and age (OR=0.89, 95% CI: 0.80 to 0.97). Factors associated with surgical drainage were age (OR=0.68 per year, 95% CI: 0.53 to 0.83) and size (OR=1.80 per cm, 95% CI: 1.41 to 2.36). Conclusions: The vast majority of children with acute lymphadenitis were managed with outpatient oral antibiotics and did not require return emergency department visits or surgical drainage. Larger lymph node size and younger age were associated with increased intravenous antibiotic initiation, unplanned return visits warranting intervention and surgical drainage.